Do patients from the Democratic Republic of Congo with schizophrenia have facial emotion recognition deficits?. (May 2019) - Kitoko, Germain Manzekele Bin; Maurage, Pierre; Peyroux, Elodie; ma Miezi, Samuel Mampunza; Gillain, Benoit; Constant, Eric
Abstract: Patients with schizophrenia can have difficulty recognizing emotion, and the impact of this difficulty on social functioning has been widely reported. However, earlier studies did not thoroughly explore how this deficit may vary according to emotion intensity, or how it may differ among individuals and across cultures. In the present study, our aim was to identify possible deficits in facial emotion recognition across a wide range of emotions of different intensities among patients with schizophrenia from the Democratic Republic of Congo (DRC). Thirty stable patients with schizophrenia and 30 healthy controls matched for age and level of education were evaluated using a validated and integrative facial emotion recognition test (TREF). A total recognition score and an intensity threshold were obtained for each emotion. Patients with schizophrenia had emotion recognition deficits, particularly for negative emotions. These deficits were correlated to the severity of negative symptoms. Patients showed no threshold deficit at the group level, but analysis of individual profiles showed marked heterogeneity across patients for the intensity of the emotion decoding deficit. Our study confirms the existence of deficits in emotion recognition for negative emotions in patients with schizophrenia, generalizes it to DRC patients, and underlines considerable heterogeneity among patients.